Evaluation of landfill gas emissions from municipal solid waste landfills for the life-cycle analysis of waste-to-energy pathways. (10th November 2017) - Lee, Uisung; Han, Jeongwoo; Wang, Michael
Abstract: Various waste-to-energy (WTE) conversion technologies can generate energy products from municipal solid waste (MSW). Accurately evaluating landfill gas (LFG, mainly methane) emissions from base case landfills is critical to conducting a WTE life-cycle analysis (LCA) of their greenhouse gas (GHG) emissions. To reduce uncertainties in estimating LFG, this study investigated key parameters for its generation, based on updated experimental results. These results showed that the updated parameters changed the calculated GHG emissions from landfills significantly depending on waste stream; they resulted in a 65% reduction for wood (from 2412 to 848 t CO2 e/dry t) to a 4% increase for food waste (from 2603 to 2708 t CO2 e/dry t). Landfill GHG emissions also vary significantly based on LFG management practices and climate. In LCAs of WTE conversion, generating electricity from LFG helps reduce GHG emissions indirectly by displacing regional electricity. When both active LFG collection and power generation are considered, GHG emissions are 44% less for food waste (from 2708 to 1524 t CO2 e/dry t), relative to conventional MSW landfilling. The method developed and data collected in this study can help improve the assessment of GHG impacts from landfills, which supports transparent decision-making regarding the sustainable treatment, management, and utilization of MSW. Highlights: Landfill gas emissions from specific waste streams are evaluated. Waste-to-energy pathways displace waste landfills avoiding landfill gas emission. Non-collected CH4 from landfills becomes a major greenhouse gas emission source. The life-cycle greenhouse gas emissions of waste-to-energy pathways are evaluated.